Atopic dermatitis in sickle cell children - Ashwi, Shaima; Alobaisy, Ahmad; Herzallah, Nawal; Alwaheed, Fatema; Hadi, Ibtihal; Alabbas, Duaa; Al-Rasheed, Faisal; Alshuraym, Nawaf; Alzein, Esra (International Journal Of Community Medicine And Public Health, 2018)
Sickle cell disease is an autosomal recessive disease characterized by recurrent vaso-occlusive events. Despite the genetic basis of its pathophysiology, recent researchers stated that it is an inflammatory immune-mediated disease where inflammation plays a crucial role in the initiation of adherence between sickle cells and vascular endothelial cells. Allergic, as well as infectious, inflammation is proposed to contribute to the initiation of vaso-occlusive events. Although several researchers reported an association between sickle cell disease and atopic conditions such as bronchial asthma and allergic rhino-conjunctivitis, few cases have reported an association between sickle cell disease and atopic dermatitis. Atopy was reported to be considerably linked to sickle cell disease for several reasons. Firstly, patients with sickle cell disease have higher IgE levels than the general population. Secondly, the mechanism of activation of molecular adhesion between endothelial and blood cells are similar between both sickle cell disease and atopic disease. Thirdly, the cytokines produced from platelet activation are the same cytokines that stimulate allergic inflammation in atopic diseases and promote adherence of sickle cells and endothelium in sickle cell disease. Lastly, sickle cell disease was reported to be associated with other atopic diseases.